Cross-Linking Cellular Prion Protein Induces Neuronal Type 2-Like Hypersensitivity - Adhikari, Utpal Kumar; Sakiz, Elif; Zhou, Xian; Habiba, Umma; Kumar, Sachin; Mikhael, Meena; Senesi, Matteo; Guang Li, Chun; Guillemin, Gilles J.; Ooi, Lezanne; David, Monique Antoinette; Collins, Steven; et al. (Frontiers in Immunology, 2021)
Background: Previous reports identified proteins associated with ‘apoptosis’ following cross-linking PrPC with motif-specific anti-PrP antibodies in vivo and in vitro. The molecular mechanisms underlying this IgG-mediated neurotoxicity and the role of the activated proteins in the apoptotic pathways leading to neuronal death has not been properly defined. Previous reports implicated a number of proteins, including apolipoprotein E, cytoplasmic phospholipase A2, prostaglandin and calpain with anti-PrP antibody-mediated ‘apoptosis’, however, these proteins are also known to play an important role in allergy. In this study, we investigated whether cross-linking PrPC with anti-PrP antibodies stimulates a neuronal allergenic response. Methods: Initially, we predicted the allergenicity of the epitope sequences associated with ‘neurotoxic’ anti-PrP antibodies using allergenicity prediction servers. We then investigated whether anti-PrP antibody treatment of neuronal (N2a) and microglia (N11) cell lines leads to a neuronal allergenic response. Results: We found that both tail- and globular-epitopes were allergenic. Specifically, binding regions that contain epitopes for ‘neurotoxic’ antibodies such as ICSM18 (146-159), ICSM35 (91-110), POM 1 (138-147), POM 2 (57-88) and POM 3 (95-100) lead to activation of allergenic related proteins. Following direct application of anti-PrPC antibodies on N2a cells, mass spectrometry analysis identified 4 neuronal allergenic-related proteins when compared with untreated cells. Furthermore, mass spectrometry analysis identified 8 neuronal allergenic-related proteins following cross-linking N11 cells with anti-PrPC antibodies prior to co-culture with N2a cells, when compared with untreated cells. Of importance, we showed that the allergenic effects triggered by the anti-PrP antibodies were more potent when antibody-treated microglia were co-cultured with the neuroblastoma cell line. Furthermore, in both direct and co-culture with antibody-treated microglia, we demonstrate that the allergenic proteome was part of the PrPC-interactome. Conclusions: This study showed for the first time that anti-PrP antibody binding to PrPC triggers a neuronal allergenic response (we termed ‘IgG-Mediated Neuronal Allergenic Toxicity’) and highlights the important role of microglia in triggering IgG-mediated neuronal allergenic toxicity. Moreover, this study provides an important impetus for including allergenic assessment of therapeutic antibodies for neurodegenerative to derive safe and targeted biotherapeutics.